A case of sacrococcygeal teratoma associated with antenatally acquired urethrovaginal fistula and hydrocolpos - Yuichi Shibui; Satoshi Obata; Ryuichiro Hirose; Ryo Nakano; Takashi Setoue; Takeshi Miyazaki; Hirofumi Matsuoka; Toshihiko Sato (Surgical Case Reports)
Abstract Background Sacrococcygeal teratomas (SCTs) are known to cause urological complications, but urethrovaginal (UV) fistula as a complication of SCT is rare. We herein report a case of SCT with UV fistula and hydrocolpos. Case presentation A 1-day-old female neonate presented to our department with prominent swelling in the sacrococcygeal region. She was born at 37 gestational weeks via spontaneous vaginal delivery from a 39-year-old woman. The weight of the baby was 2965 g, and her Apgar scores were 4/10 (at 1 and 5 min). An MRI examination confirmed an 11 × 11 cm Altman classification typeII SCT associated with hydrocolpos, a dilated urinary bladder, and bilateral hydronephrosis. When she was 5 days, the SCT was excised totally and a coccygectomy was performed. After the operation, as her urinary output appeared unstable, a cystoscopic examination was performed on the third postoperative day. This revealed that the UV fistula was located approximately 1 cm from the urethral opening. In addition, the proximal urethra was unobstructed and connected to the bladder. The cystoscope allowed for the passage of a urinary catheter through the urethra. After 1 month of catheter placement, she was discharged from the hospital at 57 days of age. Follow-up was uneventful, with neither urinary infection nor retention. Conclusions SCTs are associated with not only trouble with rectal function and lower extremity movement but also urinary complications. The pathogenesis of this UV fistula is thought to be the rapid growth of the SCT that developed in the fetal period, resulting in obstruction of the urethra by the tumor and the pubic bone, which in turn caused urinary retention and the formation of a fistula as an escape route for the pressure. Because SCTs can cause a variety of complications depending on the course of the disease, careful examination and follow-up are necessary.